The Role of Community Based Organization (CBO) in Community Transformation: The Case of Lukenya Pillars of Transformation (LPT), Machakos County, Kenya (Proceedings of the International Conference on Social Sciences, 2023)
Transformation is a major post COVID 19 issue of focus for Lukenya Pillars of Transformation (LPT), a student engineered Community Based Organization (CBO). The objective of this research is to enhance visibility of the CBO through highlighting and analyzing results by two interns attached to complete their post COVID 19 response on mental health issues and impact among adolescents between the ages of 11-15 years. It is expected that the research would bring visibility for the CBO to attract funding for projects. The research utilized a descriptive research design approach. Quantitative and qualitative methods were employed through the use of questionnaires and key informants. A sample size of 130 pupils filled out questionnaires and 20 key informants were interviewed on the relevant discussions that were ongoing. The pupils were selected using a census sampling method while the key informants were through purposive sampling. The quantitative data was coded and analyzed using SPSS, version 23. Qualitative data was coded and put into themes and concepts that the respondents shared, and analyzed in line with respective research objectives. From the findings, it was observed that COVID 19 lockdown affected the age group 11-15 years adversely yet mortality and morbidity were low. In the same light, some respondents did not have a clear knowledge of COVID 19. Although all pupils were affected emotionally and economically, where there was social support adaptation was positive. As a result of the findings, trainings were implemented for pupils, parents, teachers, social workers, and guardians. Funding was sought to support LPT. The study will contribute positively to applied knowledge in the area of development in Machakos County.
Keywords: LPT; visibility; research; mental health; adolescent; COVID 19.